Application of Security Situation Awareness in Network Attack Defense - Lu, Haoxuan (Journal of Theory and Practice of Engineering Science, 2025)
In the computer network technology system, the development and application of a security situational awareness model and software system can accurately adapt to the application requirements of attack and defense business functions in the computer network. The network attack defense system which is based on security situational awareness technology can reshape all kinds of network attacks, and analyze the vulnerability of computer network security vulnerabilities in the region, so it presents a visual security situation. This paper will focus on the application points of network attack defense based on security situational awareness.